19. YÜZYILDA OSMANLI DEVLETİ'NİN İDARİ TAKSİMATI (1839-1914) - ÖZKAN, ELA (Fırat Üniveristesi, 2017)
İdari yapı bir devletin temel birimidir. Bu birimin yanlış yapılanması ve işleyişi idari düzenin bozulmasında belirleyici bir etkendir. Bu nedenle bir devlet idari sistemini oluştururken idari taksimat birimlerini de doğru biçimlendirdiği sürece, güçlü ve sağlam bir idari sistemin temelleri atılır. Osmanlı Devleti de kurulduğu ilk yıllardan itibaren idari yapısını sürekli yenileyerek varlığını uzun süre korumayı başarmıştır. 19.yy dan itibaren ise siyasi vaziyetten kaynaklanan iç ve dış etkenler ile idari taksimat yeniden şekillenmiştir. Hazırladığımız tez 19.yy Osmanlı Devleti idari taksimat birimlerini yıllar arasındaki değişikliklerle ortaya çıkarmayı hedeflemiştir. Anahtar Kelimeler: 19.yy, İdari Taksimat, Vilayet, Sancak

Administirative system is the basic unit of the state. The wrong structure and functioning of the administrative system, has been a determining factor in the deterioration of the administrative order. Therefore, as long as the correct format while determining the administrative territorial units of the state administrative system, the foundations of a strong and robust administrative system will be taken. From the first years of the Ottoman Empire also established its presence by constantly innovative administrative structure has been successful for a long time protection. From the 19th century, internal and external factors resulting from the political situation and the administrative division have been reshaped. The thesis we prepared, aims to reveal the administrative divisions of the Ottoman State in the 19th century through changes between years. Key Words: 19. Century, Administrative Division, Province, Starboard
Administrative division of the Ottoman Empire in the 19th century (1839-1914)
Keywords: Tarih